Black Soldier Fly Larvae (Hermetia illucens) as a Waste Reduction Agent and an Alternative Livestock Feed - Andari, Gardis; Ginting, Nina Maksimiliana; Nurdiana, Ramdan (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
Black Soldier Fly or Hermetia illucens is an insect that is currently being studied for its characteristics and nutrient content. Black Soldier Fly comes from America which spreads to subtropical and tropical regions. BSF larvae could be develop, grow, in a various organic waste media, because their high tolerance in a pH fluctuation. Some of factors that determine the success of animal feed are the quality and nutrient content itself. The livestock industry is the largest component in the business of providing animal feed reach of 50-70%. The important component in animal feed is protein. Protein content plays an important role in body metabolism, tissue formation, and growth rate. This research aimed to detect nutrient content of BSF larvae with use of various organic waste as their growth media. Analysis of nutrient content (proximate) in larvae includes protein (Kjeldahl method), lipid (Soxhlet method), carbohydrate, and water content. The proximate analysis obtained showed the differences in each type of waste media with the average values of protein, carbohydrates, and fats, respectively, 42.63%, 21.47%, 21.38%. Protein content is the highest element in BSF larvae in all types of growing media.